Transfection of Plasmodium falciparum within human red blood cells. - Wu, Y (1995)
Plasmodium falciparum malaria parasites within human red blood cells (RBCs) have been successfully transfected to produce chloramphenicol acetyltransferase (CAT). Electroporation of parasitized RBCs was used to introduce plasmids that have CAT-encoding DNA flanked by 5' and 3' untranslated sequences of the P. falciparum hsp86, hrp3, and hrp2 genes. These flanking sequences were required for expression as their excision abolished CAT activity in transfected parasites. Transfection signals from native CAT-encoding DNA compared well with those from a synthetic DNA sequence adapted to the P. falciparum major codon bias, demonstrating effective expression of the bacterial sequence despite its use of rare P. falciparum codons. Transfected ring-stage parasites produced CAT signals at least as strong as transfected schizont-stage parasites even though ring stages are surrounded by more RBC cytoplasm than schizonts. The transfection of erythrocyte-stage P. falciparum parasites advances our ability to pursue genetic analysis of this major pathogen.